If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x) = 5.2x + -4 x = 5.2x + -4 Reorder the terms: x = -4 + 5.2x Solving x = -4 + 5.2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5.2x' to each side of the equation. x + -5.2x = -4 + 5.2x + -5.2x Combine like terms: x + -5.2x = -4.2x -4.2x = -4 + 5.2x + -5.2x Combine like terms: 5.2x + -5.2x = 0.0 -4.2x = -4 + 0.0 -4.2x = -4 Divide each side by '-4.2'. x = 0.9523809524 Simplifying x = 0.9523809524
| x^2+3x-6(3x-13+4)=y | | 4+(6)= | | -2-x=-3x+4 | | y=x^3-36x+4 | | H(x)=2x^2+9 | | 2h+12=3 | | -138=-6x-5(-4x+8) | | 28/30=x/4 | | -x=18-3x | | -6+x=-2x+6 | | 5=3+8 | | 7n-3=-9+4n | | m+4=-19 | | x+8=-42 | | 7s-13=-49+s | | 5x-30+30x=10+3x-20 | | 23x-17y=19 | | 12x-3=7x+6 | | 8/3=x | | 3x(5-6)=15 | | -8x^3-72x=0 | | .25x+9=-16 | | t/-8=-5 | | -6x-21=-129 | | (12/x)-(12/x-5)=2/x | | 95=4-9x | | -x-2=-3+4 | | 17/7=y/6 | | y-16=z | | 3:1/5 | | x-10=.85x | | -3x^2-11x+8=0 |